The environmental, economic, and social potential of industrial waste-based geopolymer materials toward the net zero emission 2050 target - Evelyn Anabela Anisa (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The construction sector significantly contributes to global CO₂ emissions, primarily from Portland cement production, accounting for about 8% of total emissions. This study explores the environmental, economic, and social potential of industrial waste-based geopolymers as a sustainable alternative to conventional concrete, supporting the Net Zero Emission 2050 target. Methods: This research adopts a qualitative literature review approach, collecting and analyzing recent studies concerning the utilization of fly ash, slag, silica fume, and waste glass as binding precursors in geopolymer synthesis. Furthermore, a comparative analysis was conducted to assess the potential for CO₂ emission reduction and cost efficiency based on several implemented projects. Findings: The findings indicate that geopolymer concrete can reduce CO₂ emissions by approximately 18%–64% and production costs by up to 30%, while maintaining comparable mechanical performance and durability to Portland cement-based concrete. Large-scale applications in several countries have demonstrated the material’s practical feasibility. From an environmental perspective, geopolymer technology substantially decreases embodied carbon; economically, it lowers maintenance expenses; and socially, it promotes green employment opportunities and enhances public awareness of sustainable construction practices. Nevertheless, the lack of standardized regulations and limited policy support remain key barriers to its broader implementation. Conclusion: Geopolymer technology demonstrates significant potential in achieving sustainable and low-carbon construction, thereby contributing to the realization of the Net Zero Emission 2050 goal. Novelty/originality of this article: The novelty of this study lies in its comprehensive integration of various industrial waste materials to holistically assess their environmental, economic, and social benefits as a unified approach toward sustainable construction.